The problem of art: technique in Benjamin’s early aesthetics (Lebenswelt. Aesthetics and philosophy of experience., 2025)
Walter Benjamin's reflection on technology and its impact on aesthetics is undoubtedly one of the most influential. Benjamin has shown us the enormous change that art is undergoing thanks to or because of new forms of artistic production such as photography and cinema. The purpose of this article is to show how Benjamin's confrontation with the technical and technological component of works of art does not actually begin with his engagement with new media. In an attempt to pursue this objective, it will be shown how the technical element and the associated crisis of traditional aesthetic values are of central importance from his earliest writings on literary criticism and philosophy of art. This will be possible by highlighting the extreme relevance of the theoretical category of "problem" in the young Benjamin, which will allow us to place him within that problem-solving culture that represents one of the most important theoretical strands of modern philosophy.
Keywords: Walter Benjamin, Aesthetics, Art, Problem, Technology